Factors contributing to course changes among students at welwitchia university in Namibia: a student nurse perspective - Kamenye, Esther; Iipinge, Scholastika; du Plessis, Denise (International Journal of Advanced Nursing Studies, 2016)
The overarching purpose of this study was to explore and describe the factors contributing to the changing of study courses among student nurses at Welwitchia University in Namibia. A qualitative explorative, descriptive and contextual research design was conducted, using individual in-depth interviews to gather information from 55 students, registered at Welwitchia University from 2013 to 2015, who had changed their course of study before joining the university. A purposeful sampling (convenience) technique was used. Interviews were conducted from October to November 2015 until the data were saturated.The results of this study established that after completing Grade 12, students enrol for any courses with no clear sense of understanding of the choice they have made just to keep themselves busy. This is mostly done when they have been rejected for their initial choice of course (nursing course) at the universities to which they have applied. The study also revealed that some students enrol for courses that are chosen for them by their families, which results in students later changing courses to one of their preference that is nursing. Others changed courses to nursing because they found the first course too difficult.The recommendations based on the findings of this study include the consideration of a gap year to take up voluntary jobs at places like old age homes, orphanage homes to practice caring activities while waiting to be admitted for the nursing course, and introducing or strengthening of career guidance at all secondary schools and institutions of higher learning.